Prevalence of gastroesophageal reflux disease among patients in klinik Rawatan Keluarga (KRK), Hospital Universiti Sains Malaysia - Noor Izati Ab, Aziz (Universiti Sains Malaysia, 2016)
The prevalence of gastroesophageal reflux disease (GERD), a chronic, painful disease known to deteriorate the quality of life of those affected is on the rise in Malaysia. Despite a common disorder, population-based data on GERD is lacking and conflicting. The aims of this study were to estimate the prevalence of GERD and its association with lifestyle factors in the adult patients of Klinik Rawatan Keluarga (KRK), Hospital USM. A cross-sectional study utilizing a validated GERD questionnaire including items on socio-demographic data was performed on 274 patients randomly sampled from the KRK from December 2015 to February 2016 to confirm GERD. Statistical analysis was done by Statistical Package for the Social Sciences (SPSS) version 20.0 and the level of significance was set at/?<0.05. Pearson Chi Square analyses were conducted to explore the association between prevalence of GERD and selected socio-demographic data. Among the study subjects 64 were male and 210 were female, with a mean age of 44.38 (SD 15.649) years. Among the study participants, prevalence of GERD was found in 61 (22.3%) and likelihood of GERD was high in female (p<0.01). Increased age, higher level of education, higher monthly household income, co-morbidity, employed subjects, and smoking were significantly associated with GERD symptoms (p<0.05). No significant association of GERD was found with gender, ethnicity, marital status, place of residence and body mass index. As a conclusion, this questionnaire based patient survey showed that GERD is not an uncommon condition in our community. Hence, there is need for health promotion on GERD to improve public understanding about GERD.